PERAN PEMERINTAH KABUPATEN BADUNG DALAM MENGELOLA RUANG TERBUKA HIJAU (RTH) DENGAN PERSPEKTIF GOOD ENVIRONMENTAL GOVERNANCE (CITIZEN CHARTER, 2022)
The problem of environmental damage is becoming the concern of many parties. The lack of a role from the government of the Badung district office in implementing green open space management, the management of green open spaces in Badung district has only reached approximately 12% of public green open spaces and where the number for private green open spaces is 18%, which is already far exceeding than required. This has the potential to experience environmental damage along with the progress of development in all fields. Therefore, the author wants to analyze this problem by raising the title